New earthworms of the Amynthas morrisi-group (Oligochaeta, Megascolecidae) from Hainan Island, China - Sun, Jing; Jiang, Ji-Bao; Zhao, Qi; Qiu, Jiang-Ping (Zootaxa, 2015)
This paper describes two new species of earthworms belonging to the Amynthas morrisi-group from Hainan Island, China: Amynthas zonarius sp. nov. and Amynthas wuzhimontis sp. nov. Both have two pairs of spermathecal pores in 5/6–6/7, and simple intestinal caeca. Amynthas zonarius sp. nov. has a pad-like male porophore, with flat-topped tubercle surrounded by 5 skin folds distal half of the spermathecal diverticulum dilated into band-shaped seminal chamber. Amynthas wuzhimontis sp. nov. has a seminal chamber constricted into moniliform subchambers and a glandular pad-like elliptical male pore porophore surrounded by the tumid area. Partial COI sequences of the holotypes of the two new species have been submitted to GenBank as DNA barcodes to enable molecular species identification.